Digitizing development: Enablers and inhibitors of mobile app-based population census adoption - Ofosu-ampong, Kingsley (Springer, 2024)
Limited understanding exists regarding the involvement of digital technologies in population and housing censuses (PHCs) or national housing survey (NHS) due to the historical dominance of paper-and-pencil interviewing (PAPI). To address this gap, this study investigates the adoption of digital census methods in Ghana's PHC using mixed-methods approach. The qualitative analysis identified challenges related to household surveys, including political interference, inadequate remuneration for census officers, financial constraints, and difficulties with software upgrades and GPS access. These inhibitors can be categorized into individual, technological, environmental and administrative factors. Quantitative findings revealed that performance expectance, social influence, facilitating conditions and organizational influence significantly influence field officers' intention to use digital census tools. Given the nascent research on digital technologies in the NHS, the empirical findings from this study provide a valuable foundation for informing their use in various countries.